Experimental Research on Mechanical Properties of High-Temperature Sandstone with Different Cooling Methods - Minglei Zhang; Runde Qiu; Lei Yang; Yuting Su (Advances in Civil Engineering)
Various tests including the longitudinal wave velocity tests and uniaxial compression tests have been conducted to evaluate the impact of cooling methods (including natural cooling, water cooling, and cooling by liquid carbon dioxide) on mechanical properties of sandstone under the natural status and high temperature. The acoustic emission signals were also monitored during the tests. According to the tests conducted, the sandstone sample density attenuation rate and the longitudinal wave velocity attenuation rate are higher than those of the specimen under natural status while the uniaxial compressive strength and Young’s modulus are lower. Comparing with the sandstone under the natural status, the compression sections of the stress-strain curves of the high-temperature sandstone samples treated by three cooling methods are longer with lower strain peak values. The order of the acoustic emission is revealed as follows: the sample cooled by liquid carbon dioxide < the sample cooled by water < sample cooled naturally < the sample under natural status, which suggests that the rapid cooling (cooled by liquid carbon dioxide) produces the severest damage on the sample, followed by the water cooling and natural cooling methods. In addition, the relationship between the sample strength weakening coefficient and the cooling rate is defined based on the statistical data of the cooling time of the high-temperature specimen under the three cooling methods.